Algebraic Models of Cubical Weak ∞-Categories with Connections - Camell Kachour (Categories and General Algebraic Structures with Applications, 2022)
In this article we adapt some aspects of Penon’s article [23] to cubical geometry. More precisely we define a monad on the category CSets of cubical sets (without degeneracies) whose algebras are models of cubical weak ∞-categories with connections.